Tendência temporal da taxa de hospitalização por tromboembolismo venoso em idosos brasileiros de 2010-2020 - Barp, Milara (2021)
INTRODUCTION: Venous thromboembolism (VTE) is a clinical condition that includes deep vein thrombosis (DVT) and pulmonary thromboembolism (PE). Approximately 60% of VTE cases worldwide affect people aged 65 years or older. In addition to the higher incidence of the disease, the older people have more frequent hospitalizations and mortality from this disease. Thus, in the older people, the disease is more challenging to health systems. Changes in the treatment of VTE in recent years, require analysis of its distribution to assess the impact on health services, considering that studies on the distribution and trend of hospitalizations in the older people are limited in Brazil. OBJECTIVE: To analyze the temporal trend of hospitalizations for venous thromboembolism (VTE) in the older people Brazilians from 2010 to 2020. METHODOLOGY: This is an ecological time series study, using secondary information from the Hospital Information System (SIH) of the Unified Health System (SUS). Hospital admission records of elderly people aged 60 years or over available at the SIH/SUS for the period 2010-2020, with a main diagnosis of VTE, were included. Prais-Winsten regression was used for trend analysis. RESULTS: There is a trend towards a decline in hospitalizations for VTE, with an annual percentage change of -40.71 (95%CI-50.46;-29.04). The decline in hospitalizations for VTE was seen in all regions, with the exception of the Northeast region, which showed a stationary trend. Reduction in hospitalizations for DVT, with an annual percentage change of -43.14 (95%CI -51.36; -33.54). There was a downward trend in hospitalizations for DVT in all regions, with the exception of the Northeast region. On the other hand, the trend of hospitalizations for PTE was ascending, with an annual percentage change of 4.33 (95%CI 1.26; 7.48). The upward trend in the country for hospitalizations for PTE was also verified in the Northeast region, however, it was stationary in the other regions. CONCLUSION : The results show a declining trend in hospitalization rates for DVT and VTE, but there was an upward trend for PTE. The study also points out differences in rates and trends between Brazilian regions.